Traditional starter cultures for enset fermentation: Unravelling their production and microbial composition. (June 2019) - Andeta, A.F.; Vandeweyer, D.; Teffera, E.F.; Woldesenbet, F.; Verreth, C.; Crauwels, S.; Lievens, B.; Vancampenhout, K.; Van Campenhout, L.
Abstract: Enset ( Ensete ventricosum ) is a drought tolerant food crop consumed in Ethiopia after fermentation into 'kocho ' . In most enset growing regions of Ethiopia, traditional starters are prepared in local households and added to the scraped enset mash to aid the fermentation. The preparation of the starters differs among ethnic groups. The aim of this study was twofold. The first objective was to obtain an overview of the preparation methods and the specific usage of the starters. To this end, a survey was conducted in eighteen districts (covering seven zones or ethnic groups) in southern Ethiopia. The second objective was to collect starter samples from these districts and characterize their microbial community based on sequencing of the V4 region of the 16S rRNA gene. The survey results showed that the main ingredients used to prepare the starters were generally the same within a zone but varied between zones. The collected starters had a pH ranging from 3.68 ± 0.16 to 5.62 ± 0.33. Plate counts showed that lactic acid bacteria were present in high numbers in samples collected from Amaro (9.07 ± 0.00 log cfu/g), Tocha (8.70 ± 0.50 log cfu/g) and Mareka (8.86 ± 0.60 log cfu/g) districts. Moreover, Enterobacteriaceae were identified in samples collected from Kochere (7.16 ± 0.30), Dale (7.08 ± 0.30), Shembedino (6.93 ± 0.60) and Wondeo Genet (6.36 ± 0.70) districts. Overall, Lactobacillus, Lactococcus and Leuconostoc were the dominant LAB genera identified in the starters. These isolates will be further considered for the development of a commercial enset starter culture.